Comoros : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews economic developments in the Comoros during 1992-95. The economic performance of the Comoros during 1991-94 was characterized by real growth of about 1.6 percent a year on average, large financial imbalances, an eroding export base, and the accumulation of large domestic and external payments arrears. The poor economic performance was particularly noticeable during 1994-95 when real GDP, which grew by about 3 percent during 1991-93, declined by about 2 percent a year, as a result of a negative terms-of-trade shock, and increased political uncertainty.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet